Pelatihan Penilaian Tumbuh Kembang Balita pada Guru PAUD dan Kader Posyandu di Desa Samuti Krueng Kabupaten Bireuen - Dewi Maritalia; Agustina Agustina; Sari Rizki; Ulva Mahera; Amuna Safura; Bila Salsabila; Ziana Abbas (Jurnal Abdimas Kesehatan (JAK), 2023)
Stunting is still a problem in Bireuen Regency. The most dominant impact of stunting is the disruption of physical growth, lack of cognitive abilities, and weak immunity of a child. There are various methods of stimulation and early detection of toddler growth and development that can be done to help children grow and develop optimally, namely screening tests which include weight measurement, head circumference measurement, developmental pre-screening questionnaire (KPSP) and mental-emotional problem deviations. Posyandu cadres have an important role because they are the ones who are close to the posyandu target activities and have more face-to-face frequency than other health workers. The Toddler Growth and Development Assessment and Monitoring Training activities were carried out from 7 to 12 August 2023 in Samuti Krueng Village with a total of 14 participants, consisting of PAUD Teachers and Toddler Posyandu Cadres. The method used was through theoretical and practical exposure. The activity went as expected. Participants were very enthusiastic in participating in the training which was carried out in theory and practice. There was an increase in the participants' post test results with the highest average score of 9.5 out of a maximum score of 15.